Primary breast leiomyosarcoma and synchronous homolateral lung cancer: a case report - Testori, Alberto; Meroni, Stefano; Voulaz, Emanuele; Alloisio, Marco; De Sanctis, Rita; Bossi, Paola; Cariboni, Umberto; De Simone, Matilde; Cioffi, Ugo (Journal of Thoracic Disease; Vol 9, No 12 (December 29, 2017): Journal of Thoracic Disease, 2017)
Radiological and histological features of breast leiomyosarcoma can mimic a wide variety of other breast lesions, such as mesenchymal tumors, breast lymphomas, poorly differentiated carcinomas and metaplastic breast carcinomas. The authors present the case of a 62-year-old woman with a primary breast leiomyosarcoma with synchronous ipsilateral lung adenocarcinoma. The latter was an incidental finding during pre-surgical staging examinations. Clinicopathological, immunophenotypic and imaging features cancer are described. A brief review of the literature on imaging findings and management of breast leiomyosarcoma is presented. The authors discuss the differential diagnoses in breast imaging and of the extra-mammary incidental findings. Surgical resection remains the cornerstone of treatment, while radiation therapy and chemotherapy remain to be defined on a single-patient basis.